Endogenous reversals of fortune - Marq Grâdésòtayn (Institute for the Study of Labor (IZA), 2008)
The phenomenon of systemic changes in the fortunes of social groups is hard to reconcile with traditional macroeconomic models of intergenerational mobility. This paper, therefore, proposes a theory of endogenous reversal of fortune, whereby instilling strict work norms is an instrument to address moral hazard in poor families more so than in rich families, which is consistent with empirical regularities pertaining to work attitudes. The mechanism implies that hard-working children of the poor may eventually overtake leisure-prone children of the rich. This evolution, in particular, of work norms, is endogenously determined and is, therefore a better explanation of the rise and the fall of population groups than existing theories that rely on exogenous ability variations.
urn:nbn:de:101:1-2008042530
Keywords: D31; 330; Work norms; intergenerational income mobility; Soziale Mobilität; Overlapping Generations; Arbeitsethik; Generationenbeziehungen; Theorie